Strength and Abrasion Properties of Mortar Incorporating Groundnut Husk Ash as Partial Cement Replacement. (2023)
This study investigated the strength and abrasion properties of groundnut husk ash (GHA) as partial cement replacement in mortar production. Groundnut husk was burnt to ashes at a temperature of 600°C to obtain Groundnut Husk Ash (GHA) and its chemical composition determined using X-ray florescence analyzer. Preparation of various mixtures of mortar were done by adopting binder/sand ratio of 1:3 and water/cement ratio of 0.5. The percentages of GHA used as replacement for cement varied from 0 - 20% at 5% increment respectively. Fresh pastes were subjected to consistency and setting time tests. Concrete cube, and prism samples were cast and cured for 7, 14, 28, 56 and 90 days and used to evaluate the compressive strength, flexural strength and abrasion resistance of mortar mixtures. The result of chemical analysis of GHA shows that the sum of percentages of SiO2, Al2O3 and Fe2O3 which forms the major oxides for a pozzolanic material was 26.98% and did not satisfied the specification for pozzolans. The GHA pastes had higher consistency and longer setting times than cement. Mortars modified with 5 and 10% GHA had higher compressive strength than the control, especially at later ages. The flexural strength and abrasion loss of mortars reduced with increase in GHA contents with 5 and 10% GHA mortars having comparable results with the control. It is concluded that GHA up to 10% is a good partial replacement of cement in mortar production.